Crea tu historia musical: creatividad, liderazgo y educación emocional en el aula = Abweichender Titel: Create Your Musical Story : Integrating Creativity, Leadership, and Emotional Learning in the Classroom - Jugo Núñez-Hoyo, Iris María (Cauriensia, 2025)
This article introduces Create Your Musical Story, an educational resource that transforms the classroom into a vibrant artistic space, encouraging students to explore their emotional, social, and civic competencies. With a strong pedagogical foundation, the project creates learning scenarios and employs Art-Based Innovation (ABI) techniques, taking students on a creative journey from the initial concept to the full production of a musical. This resource stems from the collaborative research of Iris Jugo on artistic and educational leadership, alongside the Botín Foundation, within its Education for Responsibility programme. The toolkit offers a flexible framework based on itineraries, designed to enrich various educational contexts. Aligned with the principles of Universal Design for Learning (UDL) and the Sustainable Development Goals (SDGs) for 2030, it fosters the comprehensive development of creative competencies in students. Through the application of Design-Based Research (DBR), the resource evolves with each implementation, adapting to classroom needs. During the 2023-24 academic year, the pilot phase was evaluated in six centres across Spain, Mexico, and Chile, demonstrating how our tool can make a real impact on emotional education and artistic leadership.